Pluchea indica less leaves extract as a root canal irrigant against Enterococcus faecalis colonies: ex vivo study - Fibryanto, Eko; Tio, Abdil; Gunawan, Juanita Amaludin; Hidayat, Adi; Mohd Noh, Nur Zety (CRC Press, Taylor & Francis Group, 2024)
Enterococcus faecalis is the most prevalent bacteria in root canals. One of the herbal solutions that can be used as antibacterial irrigation is Pluchea indica Less leaves. This study aims to analyze the antibacterial effects of P. indica L. leaves extract with concentrations of 12.5%, 25%, and 50% as a root canal irrigant against E. faecalis. Twenty-four sound human mandibular first premolars were endodontically prepared and inoculated with E. faecalis, then randomly allocated into six groups. Test groups were irrigated either with 12.5%, 25%, or 50% concentrations of the extract. The control groups were irrigated with either 1.25% and 5.25% NaOCl, or PBS. The inhibition test was conducted using the agar diffusion method and the number of bacterial colonies remaining in the root canal after irrigation was measured with the plate count method. The differences in antibacterial activity and the number of colonies between groups were analyzed using a one-way analysis of variants (ANOVA) test and post-hoc Tukey test (p<0.05). There were significant differences in the number of E. faecalis colonies between groups (p<0.05). The E. faecalis colony was found to be absent in the 1.25% and 5.25% NaOCl groups. The number of E. faecalis colonies in 12.5%, 25%, and 50% concentrations of the P. indica L. leaves extract was 13.2 ± 1.6 × 105CFU/mL, 9.90 ± 1.32 × 105CFU/mL, and 3.1 ± 2.08 × 10 CFU/mL, respectively. The 50% concentration of the P. indica L. leaves extract showed the best results in inhibiting growth and reducing the amount of E. faecalis colonies in the root canal.